Impact of Agricultural Land Use on Organic Carbon Content in the Surface Layer of Fluvisols in the Vistula River Floodplains, Poland - Miroslaw Kobierski; Krystyna Kondratowicz-Maciejewska; Beata Labaz (Agronomy)
Floodplains with fluvisols in Poland are crucial areas for both agriculture and environmental relevance. The largest areas of fluvisols are located in the floodplains of the Vistula River and have been identified as significant reservoirs of organic carbon. Humic substances were determined using the following procedure: Cdec—carbon after decalcification, CHA+CFA—carbon of humic and fulvic acids (extracted with 0.5 M NaOH solution), CFA—carbon of fulvic acids (extracted with 2 M HCl solution), CHumin—proportion of carbon in humins. The extraction of soluble organic matter (DOC and DON) was also determined. In the surface layer of grasslands, significantly higher mean contents of total organic carbon (TOC) and total nitrogen (Nt) were found compared with arable soils. In fluvisols used as grasslands, compared to the arable soils, significantly higher contents of Cdec, CHA, CFA, Chumin, DOC, DON, and C-stock were observed. The study results indicate that the agricultural use of environmentally valuable lands, such as floodplains, affected the stock of organic carbon and the properties of the humic substances. Grasslands stored significantly more SOC (10.9 kg m−2) than arable soils (6.7 kg m−2), emphasizing their role as organic carbon resevoirs. Agricultural practices such as limiting plowing and introducing grasslands can support carbon sequestration. Therefore, the role of fluvisols in floodplains in carbon sequestration should be emphasized in climate change mitigation strategies.